2018
DOI: 10.3390/cryst8020105
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Robust 3D Graphene–Hydroxyapatite Hybrid Bioscaffolds with Enhanced Osteoconductive and Biocompatible Performance

Abstract: In this paper, we describe three-dimensional (3D) hierarchical graphene-hydroxyapatite hybrid bioscaffolds (GHBs) with a calcium phosphate salt electrochemically deposited onto the framework of graphene foam (GF). The morphology of the hydroxyapatite (HA) coverage over GF was controlled by the deposition conditions, including temperature and voltage. The HA obtained at the higher temperature demonstrates the more uniformly distributed crystal grain with the smaller size. The as-prepared GHBs show a high elasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…They found that substrate surface decoration with nanodiamond particles not only promoted mineralization capability and osteogenic metabolic activities but also hampered protein adsorption and subsequently fibrous capsule formation and progression of chronic inflammation via improvement of the surface hydrophilicity . One of the advantages of using the NP assembly method for modification of scaffolds is that it increases the roughness and hydrophilicity of surface, thereby increasing affinity of adhesive molecules onto the surface of substrates . To achieve this goal, Chen et al prepared SF‐NP‐decorated PLLA composite scaffolds through the phase‐inversion technique using supercritical carbon dioxide.…”
Section: Surface Modification Methodsmentioning
confidence: 99%
“…They found that substrate surface decoration with nanodiamond particles not only promoted mineralization capability and osteogenic metabolic activities but also hampered protein adsorption and subsequently fibrous capsule formation and progression of chronic inflammation via improvement of the surface hydrophilicity . One of the advantages of using the NP assembly method for modification of scaffolds is that it increases the roughness and hydrophilicity of surface, thereby increasing affinity of adhesive molecules onto the surface of substrates . To achieve this goal, Chen et al prepared SF‐NP‐decorated PLLA composite scaffolds through the phase‐inversion technique using supercritical carbon dioxide.…”
Section: Surface Modification Methodsmentioning
confidence: 99%
“…Biocompatibility and bioactivity tests are currently under progress to assess the biological properties of these novel and promising biomaterials [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…This table highlights the variation in mechanical properties due to testing mechanism, graphene synthesis methods, and the addition of natural and synthetic polymers. CVD GF has been shown to support the growth of ATDC5 chondroprogenitor cells, C2C12 mouse myoblast cells, [14] MC3T3-E1 osteoblasts [25] , hMSCs, [15]–[17][26] and neural stem cells. [18] The mechanical properties of CVD GF are dependent on both the template structure and the density of graphene deposited on the template.…”
Section: Resultsmentioning
confidence: 99%
“…[24] GF’s surface chemistry can be altered using various biopolymers to tune its strength and surface energy characteristics to meet the requirements of different cell lines. [17][25][26] The electrical properties of GF allow for electro-mechanical stimulation and it has been shown that the conductivity of GF remains stable with no production of harsh byproducts, unlike conductive polymers. [27] Finally, graphene materials demonstrate antibacterial and antifungal properties in wound infection, suggesting potential for anti-infective properties in tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%